Machine learning fundamentals Use Python and scikit-learn to get up and running with the hottest developments in machine learning - Saleh, Hyatt (Packt Publishing, 2018)
As machine learning algorithms become popular, new tools that optimize these algorithms are also developed. Machine Learning Fundamentals explains the scikit-learn API, which is a package created to facilitate the process of building machine learning applications. By explaining the differences between supervised and unsupervised models and by ...